Prevalencia y factores de riesgo de la somnolencia excesiva diurna y su relación con la nota promedio en estudiantes de medicina de la Universidad de las Américas - Rodríguez Ayala, Montserrat Stefany (2018)
Background: Traditionally, medical students do not sleep enough hours. Most of them should study at night and, as a consequence, they have excessive daytime somnolence that could produce attention disorders that affect their life quality and academic performance. Objective: To determine the number of students of Universidad de Las Américas with excessive daytime somnolence, their sleep quality and the relation existing between this sleep disorder and their academic performance, measured by their score. Besides, we studied some possible risk factors associated with this disorder. Methods: This investigation is an observational and prevalence (cross-sectional) study. Once we obtained their consent, we applied a general questionnaire to collect general data such as age, toxic habits, medicine intake and academic activities. Besides, we used Epworth Somnolence Scale (ESS), self-administered questionnaire, validated in spanish, to classify those students with and without excessive daytime somnolence (EDS). The Pittburgh Sleep Quality Index (PSQI) was used to assess sleep quality and the International Physical Activity Questionnaire (IPAQ) to evaluate their physical activity levels. On other hand, it has been applied statistical methods to make comparisons between these two groups (comparison of proportions), we calculated 95 % confidence intervals for point estimates such as means of age, genre and year of medical school. Simple linear and logistic regression was performed to identify the relationship between excessive daytime sleepiness and students' scores and for the identification of risk factors.